Pedagogical control of special training of professional basketball players based on measurement procedures and testing - Mokrousov, E.; Sholopa, M. (Annals of the University Dunarea de Jos Galati, Fascicle XV: Physical Education and Sport Management, 2017)
The given paper summarizes the experience of using special training control professional basketball players, the approximate content of measurement procedures and tests used for the pedagogical control of basketball players. The monitoring of the functional condition is accomplished by using tests which shall provide information for coaches on the impact of training on the body, and will help to choose the optimal strategy for training the athletes. Also, the organization of the pedagogical control of the special training of basketball players is described.